Polymer blends and composites : chemistry and technology - Muralisrinivasan, Natamai Subramanian (John Wiley & Sons ; Scrivener Publishing, 2017)
Because it is critically important to manufacture quality products, a reasonable balance must be drawn between control requirements and parameters for improved processing method with respect to plastics additives. An important contribution to the commercial polymer industry, Polymer Blends and Composites is one of the first books to combine plastics additives, testing, and quality control. The book is a comprehensive treatise on properties that provides detailed guidelines for selecting and using blends and composites for applications. A valuable resource for operators, processors, engineers, chemists, the book serves to stimulate those already active in natural polymer composites.
Keywords: Polymers.; Composite materials.; elektronické knihy; electronic books